Extraction and pre-concentration of platinum and palladium from microwave-digested road dust via ion exchanging mesoporous silica microparticles prior to their quantification by quadrupole ICP-MS - Nischkauer, Winfried (Mikrochim Acta, 2015)
We report on the use of mesoporous silica microparticles (μPs) functionalized with quarternary amino groups for the isolation of platinum and palladium tetrachloro complexes from aqueous road dust digests. The μPs have a size ranging from 450 to 850 nm and are suspended directly in the aqueous digests, upon which the anionic Pt and Pd complexes are retained on the cationic surface. Subsequently, the μPs are separated by centrifugation. Elements that cause spectral interferences in ICP-MS determination of Pt and Pd can be quantitatively removed by adding fresh 0.240 mol L(−1) HCl to the μPs and by repeating the centrifugation step. The analyte-loaded μPs are then dissolved in 0.1 mL of 2 mol L(−1) HF, diluted to 2 mL, and the solutions thus obtained are analyzed by quadrupole ICP-MS. This method avoids analyte elution from the sorbent. This “dispersed particle extraction” approach yielded a run-to-run relative standard deviation ≤ 5 % for Pt and ≤ 4 % for Pd (at 0.1 ng mL(−1), n = 4 road dust digests). Method detection limits (expressed as concentrations in the dust samples) are 2 and 1 ng g(−1) for Pt and Pd, respectively. The method was validated by analysis of a reference material (BCR CRM 723) and applied to the analysis of road dust samples collected in downtown Vienna. Pt and Pd concentrations in samples collected in summer and in winter were compared, with concentrations ranging from 205 to 1445 ng g(−1) for Pt and from 201 to 1230 ng g(−1) for Pd. [Figure: see text]